Dataluta: banco de dados da luta pela terra - Alves, Hugo Almeida [UNESP]; Morais, Pedro Henrique Castro de [UNESP]; Ortiz, Barbara Giovana [UNESP]; Silva, Hellen Mesquita da [UNESP]; Pereira, Lorena Iza [UNESP]; Pauli, Lucas [UNESP]; Ramos, Michele Cristina Martins [UNESP]; Silva, Renan Coelho da [UNESP]; Lima, Rodolfo Souza [UNESP]; Girardi, Eduardo Paulon [UNESP]; Paula, Ricardo Pires de [UNESP]; Fernandes, Bernardo Mançano [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In this paper we analyze some elements of the current situation of the struggle for land in Brazil from the data published in the report DATALUTA 2014. The analysis was conducted before the balance of the field demonstrations, land occupations, rural settlements, land tenure and socio-territorial movements.

Neste trabalho analisamos alguns elementos da atual conjuntura da luta pela terra a partir dos dados publicados em 2014 no Relatório DATALUTA Brasil 2013. A análise foi efetuada diante do balanço das manifestações do campo, ocupações de terras, assentamentos rurais, estrutura fundiária e movimentos socioterritoriais.
Keywords: Land occupations; Manifestations; Rural settlements; Struggle for land; Land reform; Ocupações de terra; Manifestações; Assentamentos rurais; Luta pela terra; Reforma agrária